Quantification of Cerenkov Luminescence Imaging (CLI) Comparable With 3-D PET Standard Measurements - Frezghi Habte PhD; Arutselvan Natarajan PhD; David S. Paik PhD; Sanjiv Sam Gambhir MD, PhD (Molecular Imaging)
Cerenkov luminescence imaging (CLI) is commonly performed using two-dimensional (2-D) conventional optical imaging systems for its cost-effective solution. However, quantification of CLI comparable to conventional three-dimensional positron emission tomography (PET) is challenging using these systems due to both the high attenuation of Cerenkov radiation (CR) on mouse tissue and nonexisting depth resolution of CLI using 2-D imaging systems (2-D CLI). In this study, we developed a model that estimates effective tissue attenuation coefficient and corrects the tissue attenuation of CLI signal intensity independent of tissue depth and size. To evaluate this model, we used several thin slices of ham as a phantom and placed a radionuclide ( 89 Zr and 64 Cu) inside the phantom at different tissue depths and sizes (2, 7, and 12 mm). We performed 2-D CLI and MicroPET/CT (Combined small animal PET and Computed Tomography (CT)) imaging of the phantom and in vivo mouse model after administration of 89 Zr tracer. Estimates of the effective tissue attenuation coefficient (μ eff ) for 89 Zr and 64 Cu were ∼2.4 and ∼2.6 cm −1 , respectively. The computed unit conversion factor to %ID/g from 2-D CLI signal was 2.74 × 10 −3 μCi/radiance estimated from phantom study. After applying tissue attenuation correction and unit conversion to the in vivo animal study, an average quantification difference of 10% for spleen and 35% for liver was obtained compared to PET measurements. The proposed model provides comparable quantification accuracy to standard PET system independent of deep tissue CLI signal attenuation.